Critical analysis of evaluation model LOMCE - José Luis Bernal Agudo (ADIDE Federación, 2015)
The evaluation model that the LOMCE projects sinks its roots into the neoliberal beliefs, reflecting a specific way of understanding the world. What matters is not the process but the results, being the evaluation the center of the education-learning processes. It presents an evil planning, since the theory that justifies the model doesn't specify upon coherent proposals, where there is an excessive worry for excellence and diversity is left out. A comprehensive way of understanding education should be recovered.